Pengaruh E-Commerce, Sistem Informasi Akuntansi, Lingkungan Keluarga, dan Locus of Control terhadap Minat Berwirausaha Mahasiswa - Stevany Angelia Manik; Usman, Berto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to empirically test the influence of e-commerce variables, accounting information systems, family environment, and locus of control on students' entrepreneurial interests. The research population comprises active undergraduate Accounting students at Bengkulu University who have taken entrepreneurship courses. The sampling technique used was purposive sampling, and the respondents consisted of 137 Bachelor of Accounting students from Bengkulu University. Data for this research were collected through a questionnaire distributed to respondents using a Google form. Data analysis was performed using SmartPLS 4.0. The research findings indicate that the e-commerce variable does not affect students' interest in entrepreneurship. Conversely, the variables of accounting information systems, family environment, and locus of control show a positive effect on the interest in entrepreneurship among Bachelor of Accounting students at Bengkulu University.